The Role of Entrepreneurial Role Model Influencer and Entrepreneurship Education towards Entrepreneurial Intention - Kylie Julia Ahmad; Cliff Kohardinata; Clarissa Rachmadella Roshidawati (Primanomics : Jurnal Ekonomi & Bisnis, 2021)
The purpose of this research is to find out the effect of entrepreneurial role model influencer and entrepreneurship education towards entrepreneurial intention. The concept of entrepreneurial role model influencer combines the concept of social media influencer with entrepreneurial role model, this is new variables and have never been used in any research. This research uses a multiple linear regression approach, the sample of this research is 153 International Business Management students of Ciputra University. The result of this research shows that the entrepreneurial role model influencer and entrepreneurship education have a significant impact on entrepreneurial intention.